Pengaruh Literasi Keuangan Syariah, Persepsi Kemudahan, Persepsi Kegunaan, Fitur Layanan dan Keamanan Terhadap Minat Menggunakan E-Money Linkaja Syariah (Studi Kasus pada Generasi Z di Kota Serang) - Mukhsin, Moh; Atiah, Isti Nuzulul; Bahtiar (Universitas Muhammadiyah Surabaya, 2025)
This research aims to analyze the influence of sharia financial literacy, perceived convenience, perceived usefulness, service features and security on interest in using LinkAja Syariah e-money among generation Z in Serang City. This research uses a quantitative approach with associative methods. Primary data was collected through questionnaires distributed to 290 generation Z respondents using cluster sampling techniques. Partial test results show that sharia financial literacy, perceived convenience, perceived usefulness, and service features have a positive and significant effect on interest in using LinkAja Syariah e-money. However, the security variable has no significant effect. Simultaneous test results state that all variables together have a significant effect on interest in use. These findings reinforce the importance of sharia literacy and perceived ease of technology in encouraging the adoption of e-money based on sharia principles. Keyword: E-Money, Interest in Using, LinkAja Syariah, Perception of Convenience, Perception of Usefulness, Security, Service Features, Sharia Financial Literacy